Distribution and phenotype of GJB2 mutations in 102 Sicilian patients with congenital non syndromic sensorineural hearing loss. (August 2014) - Salvago, Pietro; Martines, Enrico; La Mattina, Eleonora; Mucia, Marianna; Sammarco, Pietro; Sireci, Federico; Martines, Francesco
Abstract: Objective: To evaluate the frequency of GJB2 mutations and their correlation with phenotype in Sicilian non-syndromic sensorineural hearing loss (NSHL) patients. Design: Sequencing of the coding region, basal promoter, exon 1, and donor splice site of the GJB2 gene; screening for the presence of the two common GJB6 deletions. Study sample: A cohort of 102 Sicilian NSHL patients. Results: Fifteen different mutations in GJB2 and seventeen different genotypes were detected. No GJB6 mutations were found. The hearing impairment was profound in the 64.72% of probands (mean PTA0.25–4 kHz of 88.82 ± 26.52 dB HL). A total of 81.37% of patients harboured at least one c.35delG allele; c.167delT and c.-23 + 1G> A were identified in 10.78% and the 9.8% of patients respectively; c.35delG homozygotes presented more severe hearing impairment (75.59% of profound hearing loss) and a higher mean PTA0.25–4 kHz (96.79 ± 21.11 dB HL) with respect to c.35delG/non-c.35delG and c.35delG/Wt patients (P < 0.05). Conclusions: This work underlines the role of c.35delG, c.167delT and c.-23 + 1G> A as the most frequent causes of NSHL in Sicily. The c.35delG frequency found is similar to those reported in other populations of the Mediterranean area. The analysis of genetic and audiologic data confirmed a variability in the phenotype associated to a single genotype.